Evaluasi Kepatuhan Pelaporan Satgas di PT PLN (PERSERO) Unit Induk Distribusi Sumatera Utara Melalui Klasterisasi K-Means - Natasya, Novyra Tedi; Linda, Nuramal; Dalimunthe, Riska Aulia; Siregar, R. Maisaroh Rezyekiyah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
In the era of globalization, university graduates are required to have the ability to implement knowledge in real practice, which is realized through the Field Work program. This study aims to evaluate the compliance of Task Force reporting at PT PLN (Persero) North Sumatra Main Distribution Unit (UID North Sumatra). The method used is a quantitative approach with K-Means Clustering. Compliance reporting data was obtained from internal company documents, which then went through the preprocessing and clustering stages using the K-Means algorithm, with the determination of the optimal cluster number through the Elbow and Silhouette methods. The K-Means clustering analysis results identified two groups of units with different levels of compliance. Cluster 2, consisting of UP3 Binjai and UP3 Sibolga, showed a higher and more consistent level of reporting compliance. In contrast, Cluster 1 (including UP2D, UP3 B. Barisan, UP3 L. Pakam, UP3 Medan, UP3 Medan Utara, UP3 Nias, UP3 P. Sidimpuan, UP3 P. Siantar, and UP3 Prapat) had a tendency for lower compliance. This finding indicates a difference in reporting consistency that affects the effectiveness of work safety supervision. The K-Means method is proven to help PLN management identify units with low compliance, allowing corrective actions to be prioritized appropriately.